Oat enzymes - a key to value added oat products - Jaakola, Sanna; Lehtinen, Pekka; Lehto, Satu; Vahvaselkä, Marjatta; Laakso, Simo (MTT, 2004)
Besides having excellent nutritional value, oat has versatile enzyme machinery. However, the oat enzymes have seldom been utilized to carry out desired reactions in oat or in oat containing materials. Recently, the potential of oat enzymes has been apparent in enhancement of the quality of oat and in upgrading oat for novel food applications. Lipase activity in oat grain is high even without germination and the inactivation of this enzyme is a common practice for obtaining products with adequate shelf life. However, the existence of the lipase may also be seen as a positive feature and used as an aid in the manufacture of value added oat products. For example, the lipase reaction in crushed oat materials can be adjusted so that almost all fatty acids from storage lipids are hydrolysed to yield a mixture of free fatty acids rich in linoleic acid. This free linoleic acid, unlike its esterified form, is the favoured substrate for the microbial isomerization into the specific health-promoting conjugated linoleic acid isomer (Vahvaselkä et al., 2004). Native oat grain has also been found to contain an enzyme activity converting the secondary lipid oxidation products into non-volatile form, thus reducing perceived rancidity (Lehto et al., 2003). This heat-labile aldehyde dehydrogenase type activity has been shown to decrease the content of hexanal and other volatile short-chain aldehydes by oxidizing them into corresponding less-volatile carboxylic acids. Native oat flour can thus be used as a supplement in various food formulations to reduce rancid flavour. Consequently, possibilities for utilization of oat in the food industry may be much more abundant than previously thought. Lehto, S. et al. 2003. Journal of Cereal Science 38: 199-203; Vahvaselkä, M. et al. 2004. Journal of Agricultural and Food Chemistry 52: 1749-1752.
Keywords: Ka; oat enzymes; lipase; linoleic acid; aldehyde dehydrogenase; lipid oxidation